Assessment of Influence of Materialistic Values on Consumption Innovativeness - Mishra, Manit (Indian Journal of Marketing, 2011)
Materialism has been a widely debated issue, in both oriental as well as occidental communities. The present study was aimed at an examination of the relationship between the hedonic value of materialism and the consumer behaviour parameter of consumption innovativeness through extensive literature review, as well as through empirical investigation by calculating zero-order correlation. Materialism was measured using the Richins and Dawson (1992) scale, whereas, consumption innovativeness was measured using the Hirschman (1981) scale, modified through factor analysis to fulfill the objective of the present study. The study revealed that there is a strong and significant possibility that the Indian consumers having greater materialistic tendencies would exhibit higher consumption innovativeness. The utilitarian value of the study for the industry is in the area of market segmentation, new product development and diffusion of innovation.